Scalar-tensor theories and asymmetric resonant cavities - Minotti, Fernando Oscar (2013)
The recently published experimental results indicate the appearance of unusual forces on asymmetric, electromagnetic resonant cavities. It is argued here that a particular class of scalar-tensor theories of gravity could account for this effect.